ENVIRONMENTAL PROBLEMS AND THEIR SOLUTIONS - Abdusamatova Farangiz Islomovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: The article discusses the pollution of the environment and possible solutions to these problems. It also provides insights into issues such as excessive wastefulness, littering in the streets and the spread of smoke that causes breathing difficulties and harms nature. In addition, the article explains the negative consequences of these actions and suggests ways to prevent and solve them.